2005
DOI: 10.1002/chin.200528132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Azalanstat Analogues as Heme Oxygenase Inhibitors.

Abstract: Imidazole derivatives Imidazole derivatives R 0190Synthesis and Evaluation of Azalanstat Analogues as Heme Oxygenase Inhibitors.-Compounds (VI) show the best selectivity against HO-1 of all tested compounds (some yields not given). -(VLAHAKIS, J. Z.; KINOBE, R. T.; BOWERS, R. J.; BRIEN, J. F.; NAKATSU, K.; SZAREK*, W. A.; Bioorg. Med. Chem. Lett. 15 (2005) 5, 1457-1461; Dep. Chem., Queen's Univ., Kingston, Ont. K7L 3N6, Can.; Eng.) -C. Oppel 28-132

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 1 publication
1
42
1
Order By: Relevance
“…A medicinal chemistry programme was initiated based on the lead compound, QC-1, and the topological analysis shown in figure 3. The resultant analogues were screened by an in vitro CO formation assay, using microsomal preparations from rat spleen and brain as physiological sources of HO-1 and HO-2, respectively [69]. The in vivo efficacies of some select compounds were also evaluated in mice and rats, as well as in cultured renal proximal tubule epithelial cells [70].…”
Section: Structural Conservation Of Heme Oxygenase Isozymesmentioning
confidence: 99%
See 3 more Smart Citations
“…A medicinal chemistry programme was initiated based on the lead compound, QC-1, and the topological analysis shown in figure 3. The resultant analogues were screened by an in vitro CO formation assay, using microsomal preparations from rat spleen and brain as physiological sources of HO-1 and HO-2, respectively [69]. The in vivo efficacies of some select compounds were also evaluated in mice and rats, as well as in cultured renal proximal tubule epithelial cells [70].…”
Section: Structural Conservation Of Heme Oxygenase Isozymesmentioning
confidence: 99%
“…The in vivo efficacies of some select compounds were also evaluated in mice and rats, as well as in cultured renal proximal tubule epithelial cells [70]. Initial studies identified a number of compounds that were selective for the inducible HO-1 isozyme [69]. Indeed, kinetic analyses of QC-1 and its analogues confirmed a non-competitive mode of inhibition, unlike the metalloporphyrins that compete for the heme-binding site, thus putatively minimizing the chances of cross-reactivity with other heme-binding proteins such as NOS and sGC, and increasing selectivity for the HO isozymes.…”
Section: Structural Conservation Of Heme Oxygenase Isozymesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the course of designing a series of novel HO inhibitors (Vlahakis et al, 2005;Kinobe et al, 2006), we have synthesized a number of imidazole-dioxolane compounds that share structural features with the azole antifungal agents. This raised the possibility that KTZ might derive its anticancer activity through mimicry of the actions of zinc protoporphyrin, namely HO inhibition.…”
mentioning
confidence: 99%